1989
DOI: 10.1002/jcla.1860030202
|View full text |Cite
|
Sign up to set email alerts
|

Serum pregnancy‐associated α2‐glycoprotein levels in the evolution of Hepatitis B virus infection

Abstract: Serum pregnancy-associated alpha 2-glycoprotein (alpha 2-PAG) levels were evaluated in a follow-up study of patients with hepatitis B virus (HBV) infection and compared with biochemical and virological parameters. In a study of 25 patients with acute hepatitis, an association was found between high alpha 2-PAG values, ALT levels, and HBsAg in 20 patients (80%) (P less than 0.05), 18 recovered completely, and 2 had a protracted course. In five patients serum alpha 2-PAG levels were similar to those in the contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Furthermore, both α 2 M and PZP are found to be colocalized with Aβ in the brain in Alzheimer’s disease (53, 54). It is not yet known if the elevated levels of PZP measured in women with presymptomatic Alzheimer’s disease are the consequence of a general innate immune system response, since PZP levels are reported to be elevated in several other inflammatory states including rheumatoid arthritis (55), Behçet’s syndrome (56), psoriasis (57, 58), Chagas disease (59), and viral infection (60, 61). Nevertheless, the available data strongly suggest that both α 2 M and PZP are likely to participate in Aβ homeostasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, both α 2 M and PZP are found to be colocalized with Aβ in the brain in Alzheimer’s disease (53, 54). It is not yet known if the elevated levels of PZP measured in women with presymptomatic Alzheimer’s disease are the consequence of a general innate immune system response, since PZP levels are reported to be elevated in several other inflammatory states including rheumatoid arthritis (55), Behçet’s syndrome (56), psoriasis (57, 58), Chagas disease (59), and viral infection (60, 61). Nevertheless, the available data strongly suggest that both α 2 M and PZP are likely to participate in Aβ homeostasis in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…An increase in PZP may occur in inflammatory diseases, and in HIV-1-positive persons, it was determined to be 125 ± 65 µg/mL, i.e., on average up to 0.2 g/L [35]. Similar concentration was measured in patients with hepatitis B [36]. On the other hand, in the work of Tian et al [37], immune suppression was reported in the early stage in Covid-19 patients accompanied by down-regulation of a number of proteins, including PZP-like alpha-2-macroglobulin domain-containing protein 8.…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, several neurotrophins are shared ligands of PZP and α 2 M, but the precise biological importance of these interactions is not known [12]. Pregnancy-independent expression of PZP is widely reported in diseases such as Alzheimer's disease [83, 84], Parkinson's disease [85], rheumatoid arthritis [86], Behcet's syndrome [87], psoriasis [88, 89], Chagas disease [90], viral infection [91, 92], inflammatory bowel disease [93], and cancers [94, 95]. The latter observations support the idea that the upregulation of PZP could be a general stress response that is related to chronic inflammation.…”
Section: Pzp a Dimeric α2m-like Moleculementioning
confidence: 99%